2019
DOI: 10.1186/s13028-019-0496-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between sow and piglet blood hemoglobin concentrations and stillbirth risk

Abstract: Previous studies have indicated that high piglet blood hemoglobin concentration (HbC) at birth lead to better performance later in life. The primary objective of this study was to investigate the association between sow and piglet blood HbC at farrowing. A secondary objective was to investigate the relationship between sow HbC and probability of stillbirths. Farrowings were observed in 22 sows in a Danish commercial herd. Maternal blood HbC was measured 1–3 days before farrowing using a HemoCue 201 + Hb device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
(10 reference statements)
2
3
1
Order By: Relevance
“…The stillbirth rate in this study is well in a range of the previously published results [2,6,9,[14][15][16]. Proportions of non-fresh (8.0%) and prepartum stillbirth (8.8%) in this study are in agreement with that in previous work, that is, 11.5% and 5.3%, respectively [5].…”
Section: Discussionsupporting
confidence: 91%
“…The stillbirth rate in this study is well in a range of the previously published results [2,6,9,[14][15][16]. Proportions of non-fresh (8.0%) and prepartum stillbirth (8.8%) in this study are in agreement with that in previous work, that is, 11.5% and 5.3%, respectively [5].…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of stillbirth at sow level in this study (47.9%) is higher in comparison with those in Brazil (27.8% to 33.1%) (Lucia et al, 2002;Borges et al, 2005), it is, however, similar to that in Belgium (48%) (Vanderhaeghe et al, 2010) and in Denmark (44%) (Rangstrup-Christensen et al, 2017). The stillbirth rate in this study (5.2%), is within the range of reported results (4.1%-7.5%) (Lucia et al, 2002;Borges et al, 2005;Vanderhaeghe et al, 2010;Rangstrup-Christensen et al, 2017;Bhattarai et al, 2019a;2019b). Unfavorable association between farrowing duration and stillbirth has been previously substantiated (Van Dijk et al, 2005;Canario et al, 2006;Baxter et al, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…The stillbirth rate (8.1%) found in this study is higher than that previously reported by many other authors [14,[17][18][19][20]. The proportion of litters having stillbirth(s) (59.5%) was also higher than that in any previously published articles [3,5,17,21].…”
Section: Discussioncontrasting
confidence: 75%